2007
DOI: 10.1124/mol.107.034371
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Thiazolidinedione-Dependent Cell Death in Jurkat T Cells

Abstract: Thiazolidinediones are synthetic agonists for the transcription factor peroxisome proliferator-activated receptor ␥ (PPAR␥) and are therapeutically used as insulin sensitizers. Besides therapeutical benefits, potential side effects such as the induction of cell death by thiazolidinediones deserve consideration. Although PPAR␥-dependent and -independent cell death in response to thiazolidinediones has been described, we provide evidence supporting a new mechanism to account for thiazolidinedione-initiated but P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…That CII is of importance in ROS formation is further evidenced by a recent report showing that non-steroid anti-inflammatory drugs caused ROS generation in cells, of which the majority was derived from CII (Soller et al, 2007). Moreover, ferulenol, a coumarine derivative, has been reported to affect the succinate UbQ reductase by interfering with the UbQ cycle (Lahouel et al, 2007).…”
Section: Complex II As An Anti-cancer Drug Target L-f Dong Et Almentioning
confidence: 90%
“…That CII is of importance in ROS formation is further evidenced by a recent report showing that non-steroid anti-inflammatory drugs caused ROS generation in cells, of which the majority was derived from CII (Soller et al, 2007). Moreover, ferulenol, a coumarine derivative, has been reported to affect the succinate UbQ reductase by interfering with the UbQ cycle (Lahouel et al, 2007).…”
Section: Complex II As An Anti-cancer Drug Target L-f Dong Et Almentioning
confidence: 90%
“…However, in contrast to a-TOS, its practical application as an anticancer agent is restricted, as it is also very toxic to noncancerous cells, such as hepatocytes (226). Interestingly, the anti-diabetic and antiinflammatory drug, troglitazone, which contains the atocopheryl moiety similar to a-TOS, also interferes with CII activity (186). The drug was registered, but was subsequently withdrawn from the clinic due to liver toxicity (85).…”
Section: Complex IImentioning
confidence: 98%
“…Different studies demonstrated that inhibition of complex II governs a direct apoptotic process in neurons through cell-specific pathways. It was recently shown that neurons, which require high levels of energy, are sensitive to complex II-induced OxPhos impairment and this results in a rapid ATP decrease (Mandavilli et al, 2005;Liot et al, 2009;Mbaya et al, 2010), contrary to other cell types, which did not show such a rapid ATP drop in response to complex II inhibition by a SDHC mutant or by the inhibitor thenoyltrifluoroacetate (Senoo-Matsuda et al, 2001;Ishii et al, 2007;Soller et al, 2007;Byun et al, 2008). In neurons, this ATP decrease induced by either 3-nitropropionate, aptenin or a SDHA mutant causes a profound alteration of the intracellular and mitochondrial calcium homeostasis, which then leads to an amplification of mitochondrial ROS formation by complex II and probably by other sources, DC M loss and finally neuronal apoptotic cell death (Liot et al, 2009;Mbaya et al, 2010).…”
Section: Respiratory Chain Complexes and Apoptosis A Lemarie And S Grimmmentioning
confidence: 99%